Genome-Wide Association Study Identifies Two Novel Loci Associated with Female Stress and Urgency Urinary Incontinence. Issue 3 (27th September 2021) - Cartwright, Rufus; Franklin, Larissa; Tikkinen, Kari A. O.; Kalliala, Ilkka; Miotla, Pawel; Rechberger, Tomasz; Offiah, Ifeoma; McMahon, Steve; O'Reilly, Barry; Lince, Sabrina; Kluivers, Kirsten; Post, Wilke M.; et al.
Abstract : Purpose: Genome-wide association studies have not identified replicable genetic risk loci for stress or urgency urinary incontinence. Materials and Methods: We carried out a discovery stage, case control, genome-wide association study in 3 independent discovery cohorts of European women (8, 979) for stress incontinence, urgency incontinence, and any incontinence phenotypes. We conducted replication in 6 additional studies of European ancestry (4, 069). We collected bladder biopsies from women with incontinence (50) to further investigate bladder expression of implicated genes and pathways and used symptom questionnaires for phenotyping. We conducted meta-analyses using inverse variance fixed effects models and whole transcriptome analyses using Affymetrix® arrays with replication with TaqMan® polymerase chain reaction. Results: In the discovery stage, we identified 16 single nucleotide polymorphisms genotyped or imputed at 5 loci that reached genome-wide significance (p <5×10 −8 ). In replication, rs138724718 on chromosome 2 near the macrophage receptor with collagenous structure ( MARCO ) gene (replication p=0.003) was associated with stress incontinence. In addition, rs34998271 on chromosome 6 near the endothelin 1 ( EDN1 ) gene (replication p=0.0008) was associated with urgency incontinence. In combined meta-analyses of discovery and replication cohorts, associations with genome-wide significance for these 2 single nucleotide polymorphisms were confirmed. Transcriptomics analyses showed differential expression of 7 of 19 genes in the endothelin pathway between stress and urgency incontinence (p <0.0001). Conclusions: We uncovered 2 new risk loci near the genes endothelin 1 ( EDN1 ), associated with urgency incontinence, and macrophage receptor with collagenous structure ( MARCO ), associated with stress incontinence. These loci are biologically plausible given their roles in smooth muscle contraction and innate host defense, respectively.